Introduction of cell‐free DNA screening is associated with changes in prenatal genetic counseling indications. Issue 3 (21st February 2019) - Stevens, Blair K.; Noblin, Sarah J.; Chen, Han‐Yang; Czerwinski, Jennifer; Friel, Lara A.; Wagner, Chelsea
Abstract: The introduction of cell‐free DNA screening, or non‐invasive prenatal testing (NIPT), for chromosome abnormalities has greatly impacted prenatal care since its introduction in late 2011. We aimed to evaluate the association between the introduction of cell‐free DNA screening and indication and referral patterns for genetic counseling at a large US academic medical center by comparing the percentage of each counseling indication between the time period prior to the introduction of cell‐free DNA screening (2006–2011) and following its introduction (2012–2016) using multivariable Poisson regression models. Genetic counseling indications for positive carrier screens, average risk patients, abnormal ultrasound findings, and family history indications were significantly higher following the introduction of NIPT while advanced maternal age and abnormal maternal serum screening indications dropped significantly. We also showed that the uptake of amniocentesis dropped significantly after the introduction of cell‐free DNA screening, while chorionic villus sampling uptake increased. These results provide evidence that the introduction of new genetic screening technologies is associated with a shift in genetic counseling referral indications and an increased uptake in genetic screening. Additional research is needed to explore the impact of expanded testing options on the need for genetic counseling services.